PRODUÇÃO DE SUBSTRATO A PARTIR DE TABACO PELETIZADO PARA PRODUÇÃO DE MUDAS DE CAFÉ - GOTTARDI, Gabriel Alves; GOTTARDI, Guilherme Alves; SCHWARTZ, Phillip Silva; SILVA, Matheus Anacleto Alves da; LOVERA, Carlos Alberto; FLECK, Leandro (ANAIS DO ENIC, 2025)
-